Exploring coastal climate adaptation through storylines: Insights from cyclone Idai in Beira, Mozambique - Henrique M.D. Goulart; Panagiotis Athanasiou; Kees van Ginkel; Karin van der Wiel; Gundula Winter; Izidine Pinto; Bart van den Hurk (Cell Reports Sustainability)
Summary: Coastal settlements, facing increasing flood risk from tropical cyclones (TCs) under climate change, need local and detailed climate information for effective adaptation. Analysis of historical events and their impacts provides such information. This study uses storylines to evaluate adaptation strategies, focusing on cyclone Idai’s impact on Beira, Mozambique, under different climate conditions and tidal cycles. A storyline of Idai under 3°C warming increases flood impacts by 1.8 times, while aligning Idai with spring tides amplifies these by 21 times. Combining both conditions increases impacts beyond 37 times. An adaptation strategy combining flood protection and accommodation measures reduces impacts by maximum 83%, while a seawall strategy reduces these by 10%. By offering localized, detailed information, storylines can be used to measure the effectiveness of adaptation strategies against extreme events, evaluating their robustness across different scenarios, and quantifying residual impacts, complementing traditional climate risk assessments for informed decision-making. Science for society: Rising seas and stronger storms due to climate change pose significant threats to coastal communities. To effectively plan for adaptation against these events, local climate information is essential. Our study uses storylines—detailed narratives of potential high-impact events—to evaluate adaptation strategies based on local data. We use cyclone Idai in Beira, Mozambique, as a case study of a powerful cyclone that has caused extensive damage to a coastal city and imagine how these impacts would change under multiple scenarios. Then we calculate the reductions in impacts due to different adaptation strategies. We find that climate change and higher tides greatly increase Idai’s impacts. The effectiveness of the adaptation strategies considered varies considerably, with some significantly reducing impacts. This approach empowers communities to visualize and understand the impacts of future extreme weather events and make informed decisions on how to best adapt against these events.